(untitled) (Религиски дијалог и соработка, 2025)
This paper dives into how different religious groups got along in Ottoman Macedonia during the first half of the 19th century. Our main goal is to figure out how people’s long-held beliefs and their hopes for the future shaped relationships between Orthodox Christians and Muslims, and also the tensions that popped up among Christian groups themselves (like Greeks and Slavs). We’re looking at this through the ideas of Hans-Georg Gadamer, especially his concept of “fusion of horizons”—which helps us see how past experiences and present understandings blend together. We’re also bringing in Reinhart Koselleck’s idea of a “horizon of expectation” to show how future dreams actually influenced how these communities interacted day-to-day. The study starts by explaining Gadamer’s way of thinking about understanding, where conversations mix old and new viewpoints. Then, it explores the historical setting, describing the millet system that allowed for different religions to coexist, how people lived side-by-side, and even shared holy places. We also look at the growing friction between the powerful Greek Orthodox Church and the rising Slavic Orthodox communities. We’ll dig into specific historical moments – like Muslims and Christians together honoring the Orthodox Monastery of Saint Naum, and the mid-19th- century Tanzimat reforms that promised everyone equal rights – using this particular way of looking at things. Our main point is that these religious interactions weren’t fixed; they were more like ongoing conversations, full of both understanding and misunderstanding, all driven by each community’s unique past and their hopes for what was to come. Ultimately, using Gadamer’s perspective helps us get a richer, more detailed understanding of inter-religious relations in 19th-century Ottoman Macedonia, moving past simple stories to see the complex ways different views were handled and sometimes even brought together.